UPAYA SEKOLAH DALAM PENGUATAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH KEJURUAN - Nurlaelah, Nurlaelah; Subaik, Subaik (Dharmas Education Journal (DE_Journal), 2023)
This study aims to describe the Implementation of Islamic Religious Education and Efforts to Strengthen Islamic Religious Education at SMK Negeri 2 Barru. This type of research ai I is descriptive qualitative research. Data collection was carried out by interview, observation, and documentation methods. Data analysis techniques include data reduction, data presentation, and drawing conclusions, checking the validity of the findings is carried out by researchers, using the help of various sources, theories, methods, and observations. The subjects of the study were school principals, vice principals for curriculum, facilities and infrastructure for PAI teachers. The results of the research, discussion and analysis of data / information show that 1) Description of the Implementation of Islamic Religious Education at SMK Negeri 2 Barru with supporting factors, namely: students, teachers/educators, curriculum, extracurriculars, collaboration between parents and the school, facilities and infrastructure. 2) An overview of the school's efforts in strengthening Islamic religious education at SMK Negeri 2 Barru. The strengthening efforts carried out are strengthening efforts with supporting factors, namely aspects: students, teachers/educators, curriculum, extra-curricular and facilities and infrastructure. Thus the implementation and efforts to strengthen Islamic Religious education at SMK Negeri 2 Barru can run well.